2016
DOI: 10.21315/mjms2016.23.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, Leptin and Objectively Measured Physical Activity in Adults: A Narrative Review

Abstract: The objective of this study was to compile and analyse existing scientific evidences reporting the effects of objectively measured physical activity on the levels of adiponectin and leptin. Articles related to the effects of objectively measured physical activity on the levels of adiponectin and leptin were searched from the Medline and PubMed databases. The search was limited to 'objectively measured' physical activity, and studies that did not objectively measure the physical activity were excluded. Only Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Moreover, an inverse association between changes in MVPA and leptin levels was observed. Similar findings were reported in other intervention studies using objectively measured PA levels in adults [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, an inverse association between changes in MVPA and leptin levels was observed. Similar findings were reported in other intervention studies using objectively measured PA levels in adults [14].…”
Section: Discussionsupporting
confidence: 91%
“…In regard to this, several intervention studies reported a decrease of leptin levels after aerobic PA in obese adolescents [11–13]. Thus, increased physical activity, specifically MVPA, may lead to a decrease of leptin levels [14]. To our knowledge, few studies have evaluated the effect of lifestyle interventions on changes in objectively measured PA levels in obese children at high metabolic risk [4, 15–19].…”
Section: Introductionmentioning
confidence: 99%
“…49 Walking and biking are also inversely related to circulating concentrations of leptin, TNF-α and IL-6. 47,50 Although light to moderate intensity of leisure time PA (such as during daily life activities) significantly improves adipokine levels, a longitudinal cohort study reported that increased moderate to vigorous PAs were linked to significantly higher levels of adiponectin and lower levels of leptin, IL-6 and resistin. 41 The magnitude of such changes was independent of race and ethnicity or gender.…”
Section: Leisure Time Pamentioning
confidence: 99%
“…Furthermore, the GLUT4 gene expression was also increased in these animals. Another study published by the same group of researchers [ 111 ] showed that serum levels of TNF-α and interleukin-6 were reduced with training, accompanied by an increase of adiponectin [ 112 ]. However, obese subjects undergoing strength training showed improvement in insulin sensitivity even without changes in serum levels of proinflammatory cytokines [ 113 ].…”
Section: How To Deal With the Enemymentioning
confidence: 99%